The Experimental Investigation and Nonlinear Regression Analysis of the Effect of Tire Inflation Pressure on Pitch Force - Faruk Emre Aysal; Zekeriya Gi̇rgi̇n; Hüseyin Bayrakçeken; Mustafa Babagi̇ray (International Journal of Automotive Science and Technology, 2021)
In this study, the effect of tire inflation pressure on the vehicle during braking was investigated experimentally. The experimental study was carried out in the Brake-Suspension Test Device designed as a half-vehicle model, which enables vehicle brake tests to be performed in the laboratory. During the tests, a total of nine different tire inflation pressures from 26 psi to 40 psi standard value were taken into consideration. As a result of the experiments carried out separately for each tire inflation pressure, a curve characterizing the effect of different pressure values on the pitching force was obtained. Based on the experimental results, dif-ferent mathematical models suitable for the curve obtained are derived by non-linear curve fitting. For the nonlinear curve fitting process, a hybrid iterative re-gression algorithm obtained by combining classical curve fitting algorithm with Newton-Raphson iteration method was used. It was observed that the correlation coefficients (R2) of the mathematical models obtained provided sufficient sensi-tivity to express the problem under consideration.